Autonomní neuropatie gastrointestinálního traktu - Olsovský, J (Vnitrni lekarstvi, 2011)
The paper focuses on the issues of diabetic autonomic neuropathy in the gastrointestinal tract. It describes the aethiopathogenesis of diabetic polyneuropathy. More detailed discussion is then provided with respect to gastrointestinal tract. The clinical picture and options available for the diagnosis and treatment when various parts of the gastrointestinal tract are involvement are examined.
Keywords: nemoci autonomního nervového systému; diabetické neuropatie; Autonomic Nervous System Diseases; lidé; Diabetic Neuropathies; gastrointestinální nemoci; Gastrointestinal Diseases; Humans